2021
DOI: 10.1186/s13287-021-02540-1
|View full text |Cite
|
Sign up to set email alerts
|

Microfragmented adipose tissue is associated with improved ex vivo performance linked to HOXB7 and b-FGF expression

Abstract: Introduction Adipose tissue (AT) has become a source of mesenchymal stromal/stem cells (MSC) for regenerative medicine applications, in particular skeletal disorders. Several enzymatic or mechanical procedures have been proposed to process AT with the aim to isolate cells that can be locally implanted. How AT is processed may impact its properties. Thus, we compared AT processed by centrifugation (C-AT) to microfragmentation (MF-AT). Focusing on MF-AT, we subsequently assessed the impact of syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Interestingly, HOXB7 turned out to be an “universal MSC” HOX gene as it was reported to be expressed in all the different types of MSCs ( Liedtke et al, 2010 ; Klein et al, 2013 ; Foppiani et al, 2019 ). An induced expression of HOXB7 was identified as a master player driving proliferation and differentiation of human BM- and AT-MSCs ( Foppiani et al, 2019 ; Casari et al, 2021 ), and accounts for the high proliferation and sprouting potential of VW-MSCs ( Klein et al, 2013 ; Klein, 2016 ). However, rather than accounting for stem cell type-specific functions, HOX genes specify various regional properties of a tissue along the rostral-caudal axis by regulating a wide range of cellular activities such as proliferation and differentiation, cellular adhesion, migration and invasion, as well as cell death ( Parrish et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, HOXB7 turned out to be an “universal MSC” HOX gene as it was reported to be expressed in all the different types of MSCs ( Liedtke et al, 2010 ; Klein et al, 2013 ; Foppiani et al, 2019 ). An induced expression of HOXB7 was identified as a master player driving proliferation and differentiation of human BM- and AT-MSCs ( Foppiani et al, 2019 ; Casari et al, 2021 ), and accounts for the high proliferation and sprouting potential of VW-MSCs ( Klein et al, 2013 ; Klein, 2016 ). However, rather than accounting for stem cell type-specific functions, HOX genes specify various regional properties of a tissue along the rostral-caudal axis by regulating a wide range of cellular activities such as proliferation and differentiation, cellular adhesion, migration and invasion, as well as cell death ( Parrish et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bringing into sharp focus MF-AT, Casari et al afterward evaluated the effect of synovial fluid (SF) alone on both MF-AT and isolated AT-MSC to better comprehend their cartilage repair processes. The findings of this study showed that MF has a positive impact on the preservation of AT histology and might activate the expression of trophic factors that ameliorate tissue repair by processed AT [19].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 71%
“…Casari et al [19] These authors compared adipose tissue (AT) processed by centrifugation (C-AT) to microfragmentation (MF-AT). They evaluated the impact of synovial fluid (SF) alone on both MF-AT and isolated AT-MSC to better comprehend their cartilage repair processes.…”
Section: Keppie Et Al [1] 2021mentioning
confidence: 99%